2022
DOI: 10.1016/j.bbih.2021.100407
|View full text |Cite
|
Sign up to set email alerts
|

Brain-immune axis regulation is responsive to cognitive behavioral therapy and mindfulness intervention: Observations from a randomized controlled trial in patients with Crohn's disease

Abstract: Background and aims Crohn's disease (CD) is a chronic inflammatory bowel disease associated with psychological stress that is regulated primarily by the hypothalamus-pituitary-adrenal (HPA) axis. Here, we determined whether the psychological characteristics of CD patients associate with their inflammatory state, and whether a 3-month trial of cognitive-behavioral and mindfulness-based stress reduction (COBMINDEX) impacts their inflammatory process. Methods Circulating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Within this biopsychosocial framework, it has been proposed that psychological stress can contribute to relapse and exacerbation of CD symptoms. Accordingly, stress may adversely affect mucosal barrier and immune functions, leading to worsening of inflammation of the gastrointestinal tract 22–24 . Consistent with this, studies have shown that the presence and severity of fatigue and abdominal pain in patients with CD are affected by both gastrointestinal and psychological factors 6,13 ; thus, highlighting the need for combining medical care with psychological treatment.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Within this biopsychosocial framework, it has been proposed that psychological stress can contribute to relapse and exacerbation of CD symptoms. Accordingly, stress may adversely affect mucosal barrier and immune functions, leading to worsening of inflammation of the gastrointestinal tract 22–24 . Consistent with this, studies have shown that the presence and severity of fatigue and abdominal pain in patients with CD are affected by both gastrointestinal and psychological factors 6,13 ; thus, highlighting the need for combining medical care with psychological treatment.…”
Section: Introductionmentioning
confidence: 78%
“…We previously reported that a specifically designed psychological intervention, consisting of cognitive‐behavioural and mindfulness‐based stress reduction with daily exercise (COBMINDEX) diminishes psychological stress in patients with CD 25 . Moreover, COBMINDEX related‐improvement in psychological outcomes was associated with a significant reduction in inflammatory markers of CD 23 …”
Section: Introductionmentioning
confidence: 99%
“…One of the studies considered variables consequent to the pandemic, such as perceived present and future infection risk, loss of income, and financial worry [51], while another research conducted in Italy by Invito et al [52] took into account psychological distress and viral contagion beliefs, and added epidemiological characteristics, such as COVID-19 diagnosis, sex status and number of COVID-19 infected and deaths according to the participant's region. Symptom interaction network theory research has spurred several papers seeking to explore the interconnections of the most recurrent physical and psychological symptoms in certain chronic conditions, such as cancer [53], HIV [54], schizophrenia [55], stroke [56], chronic pain [57] chronic bowel disease [58], multiple sclerosis [59], arterial hypertension [7], obesity [60], and COVID-19 [61].…”
Section: The Use Of Network Models In the Context Of Psychopathologymentioning
confidence: 99%
“…Lastly, psychotherapy has emerged as a novel modulator of immune-related health ( Shields et al, 2020 ). In this regard, recent studies have demonstrated that cognitive behavioral interventions could suppress the elevated expression of various inflammatory markers in both somatic illnesses and psychiatric conditions ( Nemirovsky et al, 2021 , Diaz et al, 2021 , Sundquist et al, 2021 ). The direct impact of psychosocial interventions on excessive immune activation provides another line of support for the use of this modality against COVID-19-associated hyperinflammation and its possible sequelae of increased suicide risk.…”
Section: Inflammation As a Therapeutic Target In Covid-19 And Its Rel...mentioning
confidence: 99%